What Tinnitus Therapy Outcome Measures Are Important for Patients?– A Discrete Choice Experiment - Rademaker, Maaike M.; Essers, Brigitte A. B.; Stokroos, Robert J.; Smit, Adriana L.; Stegeman, Inge (Frontiers in Neurology, 2021)
Introduction: The therapeutic rationale varies among tinnitus therapies. A recent study identified which outcome measures should be used for different types of interventions. What patients consider the most important outcome measure in tinnitus therapy is unclear. Objectives: To study the preference of the tinnitus patient for different outcome measures in tinnitus therapy. Methods: A discrete choice experiment was conducted. Participants were provided with two alternatives per choice set (nine choice sets total). Each choice-set consisted of four attributes (tinnitus loudness, tinnitus acceptance, quality of sleep and concentration). With a difference in one of three levels (increased, similar or decreased after treatment) between the alternatives. Results were analyzed with a mixed logit model. Preference heterogeneity was explored with covariates, correlating attributes and a latent class analysis. Results: One hundred and twenty-seven participants took part. In the mixed logit models we found that the choice for a tinnitus therapy was significantly affected by all levels of the outcomes, except for a similar level in concentration and tinnitus acceptance. Tinnitus loudness was considered the most important outcome measure relative to the other attributes. Preference heterogeneity was not explained by correlating attributes. The latent class analysis identified two classes. The first class was similar to the mixed logit analysis, except for a non-significance of similar quality of sleep and tinnitus acceptance. The second class showed a statistical significant preference only for increased tinnitus acceptance and similar quality of sleep. Conclusion: Based on this study, tinnitus patients consider loudness the most important outcome measure. However, there is a variance in preference as indicated by the latent class analysis. This study underlines the importance of research into tinnitus heterogeneity. Next, this study highlights the need for research into tinnitus therapies that focus on diminishing tinnitus loudness.